Life insurer cost of equity with asymmetric risk factors - Bajtelsmit, Vickie L., author; Villupuram, Sriram V., author; Wang, Tianyang, author; The Financial Review, publisher (Colorado State University. Libraries, 2015)
This study presents an improved model for estimating life insurer cost of capital with the inclusion of upside and downside risk factors and controlling for life insurer characteristics. Although various asymmetric measures of market risk have been shown to be priced factors for the broader equity market, life insurer realized equity returns include a much larger premium for bearing downside risk, even after controlling for firm characteristics and other measures of risk. Cross‐sectional regression analysis finds a positive (negative) premium for downside (upside) betas, conditional on down and up markets, respectively. Coskewness and cokurtosis are also priced factors.
Published as: The Finanicial Review, vol. 50, no. 3, July 2015, pp. 435-457, https://doi.org/10.1111/fire.12073.
Keywords: cost of equity; upside risk; downside risk; equity market; life insurance industry; prospect theory